White matter microstructure and episodic memory in adults with down syndrome: A Tract‐Based Spatial Statistics (TBSS) Study: Imaging correlates of cognition and biomarkers. (7th December 2020) - Patrick, Austin M; Hartley, Sigan L; Wu, Minjie; Dean, Douglas C; Zammit, Matthew D; Johnson, Sterling C.; Tudorascu, Dana L; Cohen, Ann; Cody, Karly Alex; Laymon, Charles M; Klunk, William E; Zaman, Shahid; et al.
Abstract: Background: Nearly all persons with Down Syndrome (DS) will show pathology of Alzheimer's Disease (AD) in their 40s. Our study of non‐demented DS individuals showed that episodic memory was the first cognitive domain to decline in this population (Hartley et al., 2014). We have shown that diffusion tensor imaging (DTI) measures of white matter (WM) microstructure are related to amyloid burden in DS (Patrick et al., 2019). The parietal (Berryhill et al., 2007), prefrontal (Fletcher et al., 1998), and medial‐temporal (Nyberg et al., 1996) lobes have been shown to be involved in episodic memory. In this work, we examined the relation between white matter microstructure, assessed using tract‐based spatial statistics (TBSS), and episodic memory. Method: DTI scans (b = 1000 s/mm 2 and 48 encoding directions) of 43 adults (N = 43; mean age = 39.8+/‐7.0 years) with DS were acquired at 3T at two imaging sites in the Alzheimer's Biomarker Consortium‐Down Syndrome. A composite score of episodic memory was calculated based on summing the z‐scores of the 1)Free and Cued Recall test (Buschke et al., 1984), a measure of verbal episodic memory and the 2)Rivermead Behavioural Memory Test for Children‐Picture Recognition (Wilson et al., 1991), a measure of visual episodic memory. Voxelwise statistical analyses of fractional anisotropy (FA) and mean diffusivity (MD) were carried out using TBSS. The associations between episodic memory with FA and MD were analyzed using a general linear model in FSL, controlling for imaging site and baseline intelligence assessed using the Peabody Picture Vocabulary Test (Dunn et al., 2007). Result: Adjusting for site, baseline intelligence, and multiple comparisons, episodic memory and FA were significantly (p<.05) positively correlated in the right occipital, parietal, and temporal regions and bilateral prefrontal regions. MD and episodic memory were significantly negatively correlated in much of the association white matter in all lobes and survived additional correction for age. Conclusion: Our results show significant correlations of episodic memory with FA and MD in multiple areas. There is a strong correlation of both FA and MD with age, which makes disentangling age and AD‐related neurodegeneration difficult; however, these results suggest FA and MD as potential indicators of episodic memory decline in DS populations.